Thermal modelling of LSF floor systems made of lipped channel and hollow flange channel section joists. (13th September 2017) - Steau, Edward; Keerthan, Poologanathan; Mahendran, Mahen
ABSTRACT: Buildings that are not designed to have fire safety measures are not able to endure the extreme conditions in a fire event. Hence considerably more attention is being placed on the fire safety of buildings in recent times. Light gauge steel framed (LSF) floor systems are commonly used in buildings as they provide significant benefit by reducing weight and cost while increasing construction efficiencies. To obtain a satisfactory fire resistance level, floor systems must comply with a number of requirements specified in codes relating to fire resistance level. However, to understand the heat transfer process within LSF floor systems usually requires numerous complex fire tests. These tests are extremely expensive and time consuming. Therefore three‐dimensional finite element models were developed and used in this study to investigate the heat transfer in LSF floor systems made of different joist sections such as Lipped Channel and Hollow Flange Channel beam sections. Standard fire curve was defined as an amplitude curve following a time‐temperature profile based on ISO 834 standard fire curve. The time‐temperature curves obtained from the finite element analyses were compared with available experimental results to determine their accuracy in predicting the heat transfer in LSF floor systems made of the two chosen joist sections. Results showed that the proposed three‐dimensional finite element models can accurately predict the heat transfer of LSF floor systems made with lipped channel and hollow flange channel section joists. They also highlighted the differences in the thermal performance when different joist types are used. This paper presents the details of a three‐dimensional thermal modelling study of LSF floor systems made of lipped Channel and hollow flange channel section joists and the results. Innovative LSF floor systems were also proposed using the validated thermal models to enhance the fire resistant rating.